BAHASA SUNDA DIALEK PRIANGAN - E Zaenal Arifin (Pujangga: Jurnal Bahasa dan Sastra, 2016)
ABSTRACT This research "The Sundanese Dialect Priangan" aims to collect and analyze the data of Sundanesevocabularies, phrases, and sentences commonly used in Priangan (Bandung, Cianjur, Sumedang, Garut,Tasikmalaya, and Ciamis). The method used is a qualitative descriptive method. The theory used isSociolinguistics, mainly related to variations in language, manner, barrel, and dialects as well as pragmatics,such as speech acts locutionary, illocutionary, and perlocutionary, and also the principle of cooperation,such as the maxim of quality, maxim of quantity, maxim of relevancy, and maxim of manner. Due to the feudalsystem in some ethnic groups in Indonesia and the Balinese caste system in ancient times, in Sundanesesociety also appears stages in language (railroad-rafter Language). There are different vocabularies,phrases, and sentences that are different from the Banten dialect, Cirebon dialect, and others, especially inthe writing, using, and pronunciation.Keywords: variety of languages, dialects, varieties, barrel, harsh, moderate, polite.